Composite conductive film and preparation method thereof
By designing a different surface profile on the support layer of the composite conductive film, forming a gas-accommodating cavity, the problem of film adhesion during the winding process is solved, and the yield rate of roll-to-roll processing is improved.
Patent Information
- Application Number
- CN202411977365.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
During the winding process, existing composite fluids are prone to sticking due to the film surface being too smooth, causing the coating to fall off or the film to break, affecting subsequent processing.
A composite conductive film is designed with a support layer having a different surface profile in the thickness direction to form a cavity for gas accommodating to improve the problem of film adhesion during roll-to-roll processing.
Through the asymmetrical support layer profile difference, an asymmetric conductive layer structure is formed, so that the two composite conductive films have a gas-accommodating cavity after contact, effectively reducing the vacuum degree after the film surface is bonded and improving the film adhesion problem.
Smart Images

Figure CN119786622A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to current collectors, and more specifically, relates to a composite conductive film and a preparation method thereof. Background Art
[0002] The safety of lithium-ion batteries has always been a concern for end users. Lithium-ion batteries are generally safe, but if used, charged improperly or damaged, they may pose a risk of fire or explosion, especially when the current specific energy density of lithium batteries is close to its theoretical limit. Many methods have been proposed in the prior art to improve the safety performance of lithium-ion batteries, such as using intrinsically safe electrode materials (such as lithium iron phosphate instead of ternary positive electrode materials), adding flame-retardant electrolytes (such as solid electrolytes or non-flammable electrolytes), or using thermally stable separators. However, most of the above methods involve additional manufacturing processes and / or require the use of additional materials, which not only increases the production cost but also reduces the energy density of lithium-ion batteries.
[0003] Metal-plastic film current collector (composite current collector) can effectively ensure the safety of lithium-ion batteries under mechanical abuse without sacrificing the energy density of lithium-ion batteries. Therefore, more and more lithium battery manufacturers have begun to try to use composite current collectors to replace pure metal films as current collectors for lithium-ion batteries. Compared with metal current collectors, metal-plastic film composite current collectors are lighter, cheaper, and have better safety performance.
[0004] In the prior art, when preparing a composite current collector, a metal coating is obtained by magnetron sputtering, vapor deposition or chemical plating on a polymer original base film, and then dried and subjected to an anti-oxidation treatment to obtain a composite current collector with a sandwich structure of "metal layer-polymer layer-metal layer". At present, after the composite current collector is prepared by coating, the obtained film needs to be rolled up, especially the double-sided coated current collector. Because the surface of the film is too smooth and flat, a vacuum compaction is formed under the winding tension, which causes the film to adhere during the unwinding process, causing the coating to fall off or even the film to break. In the subsequent unwinding process, the film may also shake due to adhesion, affecting subsequent processing.
[0005] Therefore, it is urgent to design a composite conductive film to avoid adhesion of the film layer during the unwinding process of the film roll and improve the yield rate. Summary of the invention
[0006] In view of the above defects or improvement needs of the prior art, the present invention provides a composite conductive film and a preparation method thereof, wherein the surface of the support layer has different surface profiles to form air-accommodating cavities to improve the film adhesion problem during roll-to-roll processing.
[0007] To achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a composite conductive film, comprising a support layer 1 having two surfaces in a thickness direction; and a conductive layer 2 formed on at least one surface of the support layer 1; the composite conductive film formed has different contour morphologies on the two surfaces in the thickness direction, so as to form a gas-containing cavity 3 after the two layers of the composite conductive film are in contact.
[0008] Based on the above technical solution, the difference in contour morphology allows two layers of composite conductive films to have a gas accommodating cavity when they are in contact, thereby improving the problem of film adhesion.
[0009] Preferably, the two surfaces of the composite conductive film in the thickness direction have different average widths Rsm of contour units, and the difference is not less than 0.5 μm.
[0010] Based on the above technical solution, due to the difference in the average width of the surface profiles, when the two profile surfaces are in contact after winding, one side has an average width of a wider profile unit, so that gaps will be left to retain air, so as to reduce the vacuum degree after the film surfaces are bonded, thereby improving the adhesion of the film surface.
[0011] Preferably, two surfaces of the composite conductive film in a thickness direction have different surface roughness Rz.
[0012] Based on the above technical solution, the surface with different roughness can increase the gap in the matching surface, and can also increase the adhesion of related active materials in the subsequent electrode to a certain extent.
[0013] Preferably, two surfaces of the composite conductive film in the thickness direction have different average widths Rsm of profile units and different surface roughness Rz.
[0014] Based on the above technical solution, the gap in the mating surface can be further increased; the surface with greater roughness is preferably set on the side with a larger average width of the surface contour, so that the gap formed by the contour unit can be coordinated to reserve more air retention space and reduce the vacuum degree after the film surface is rolled up and bonded.
[0015] Preferably, the average width of the contour units on one surface of the composite conductive film in the thickness direction is Rsm1, which ranges from 2 to 8 μm; the average width of the contour units on the other surface is Rsm2, which ranges from 0.2 to 2 μm.
[0016] Preferably, the roughness Rz1 of one surface of the composite conductive film in the thickness direction is 0.01-0.4 times the thickness of the corresponding composite conductive film, and the roughness Rz2 of the other surface is 0.1-0.6 times Rz1.
[0017] Preferably, the thickness of the support layer 1 is set to 3-50 μm, and the material thereof is a polymer material or a graphite film, and the surface roughness thereof is above 0.5 μm.
[0018] Preferably, the conductive layer 2 has a thickness of 0.05-3 μm, and is made of one or a combination of gold, silver, copper, aluminum, nickel, and chromium.
[0019] According to another aspect of the present invention, a method for preparing a composite conductive film is provided:
[0020] When the conductive layer 2 is arranged on a single side of the support layer 1, a support layer 1 with an appropriate average width of surface contour units is selected, and the average width of the contour units on the surface of the conductive layer 2 is controlled according to the average width of the contour units on the surface of the support layer 1; when the conductive layer 2 is arranged on both sides of the support layer 1, the average widths of the contour units on the surfaces of the conductive layer 2 on both sides are controlled to form differences.
[0021] Preferably, when the conductive layer 2 is provided on a single side of the support layer 1, the support layer 1 is processed by laser etching. Laser etching can effectively carve out two asymmetric surfaces on the support layer 1. On this basis, the metal layer is deposited by evaporation, magnetron deposition, etc., to obtain a composite conductive film surface determined by the surface morphology of the support layer 1.
[0022] Preferably, when the conductive layer 2 is provided on both sides of the support layer 1, the conductive layer 2 is coated on both sides in at least one of the following ways to form different surface profiles: increasing the temperature of the target material after evaporation; increasing the temperature of the target material after evaporation; or reducing the speed of the support layer; or reducing the distance between the support layer and the target material; or using laser etching to process the support layer.
[0023] Based on the above technical solution, the temperature of the evaporation target is increased by adjusting the evaporation power, thereby increasing the energy of the particles, which is beneficial to crystal growth. Part of the crystals that form the conductive layer are recrystallized due to the high temperature, so that the crystal size formed by the particles deposited on the surface of the support layer is larger and the small-sized crystals are reduced, and then the surface contour will form a larger spacing and the surface roughness is greater; the lower the vehicle speed, the more high-temperature particles are obtained per unit time, so the greater the overall thermal energy, the larger the size of the crystal formed, and the more columnar it tends to be, which is easy to form a larger contour spacing and surface roughness; reduce the distance between the support layer and the target material; it can also increase the energy of the particles deposited on the surface of the support layer to a certain extent, thereby increasing the energy and temperature of the particles.
[0024] Furthermore, the formation of the conductive layer 2 is based on the deposition of metal particles. The energy of the target particles deposited on the surface of the support layer 1 is different, and the size of the formed crystals is also different.
[0025] Based on the above technical solution, by controlling the energy difference of the target particles deposited on the surface of the support layer, the crystal size formed by the metal particles can be controlled, which is then manifested as a difference in the surface contour units. When metal particles with greater energy are deposited on the surface of the support layer, the crystals tend to aggregate to form a relatively larger crystal size, so they have a larger contour unit gap and a gap for air retention after winding.
[0026] In general, compared with the prior art, the above technical solution conceived by the present invention provides a composite conductive film having the following beneficial effects:
[0027] 1. In the roll-to-roll production process, the composite conductive film proposed by the present invention forms a gas-accommodating cavity between two layers of the wound composite conductive film after contact. The present invention obtains an asymmetric conductive layer structure by using the asymmetric difference in the profile of the support layer, so that the two layers of the composite conductive film have a gas-accommodating cavity when they are attached, thereby improving the film adhesion problem during the roll-to-roll processing.
[0028] 2. The present invention can achieve asymmetric composite conductive film surface morphology through a variety of ways, such as controlling the surface morphology difference of the support layer, thereby obtaining the morphology difference of the conductive layer, and using laser etching to effectively carve out two asymmetric surfaces on the support layer. On this basis, the metal layer is deposited by evaporation, magnetron, etc., and the surface of the composite conductive film determined by the surface morphology of the support layer can be obtained. The present invention can create various unique asymmetric structures on the support layer, such as groove type, wavy shape, etc., and the area range of the asymmetric structure is controllable. By controlling the size of the laser etching area, the gas containing cavity can be maximized.
[0029] 3. The present invention can control the grain size of the conductive layer in different regions by forming different conductive layers. By stacking grains of different sizes, the asymmetric structure of the surface of the composite conductive film can also be achieved. When metal particles with greater energy are deposited on the surface of the support layer, the crystals tend to aggregate to form a relatively larger crystal size, so they have a larger contour unit gap and a gap for air retention after winding. Therefore, the film adhesion problem in the roll-to-roll production process can be solved without adding additional processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the supporting layer structure of the composite conductive film;
[0031] Figure 2 It is a schematic diagram of the structure of a composite conductive film with a double conductive layer.
[0032] Throughout the drawings, the same reference numerals are used to denote the same elements or structures, wherein:
[0033] 1-support layer; 2-conductive layer; 3-cavity. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] See also Figure 1 and Figure 2 The present invention provides a composite conductive film, including a support layer 1 having two surfaces in the thickness direction; and a conductive layer 2 formed on at least one surface of the support layer 1; the contour morphology of the two surfaces of the formed composite conductive film in the thickness direction is different, so as to form a gas-containing cavity 3 after the two layers of the composite conductive film are in contact.
[0036] Based on the above technical solution, the difference in contour morphology allows two layers of composite conductive films to have a gas accommodating cavity when they are in contact, thereby improving the problem of film adhesion.
[0037] Specifically, the composite conductive film has two surfaces in the thickness direction with different average widths Rsm of the contour units, and the difference is not less than 0.5 μm.
[0038] Based on the above technical solution, due to the difference in the average width of the surface profiles, when the two profile surfaces are in contact after winding, one side has an average width of a wider profile unit, so that gaps will be left to retain air, so as to reduce the vacuum degree after the film surfaces are bonded, thereby improving the adhesion of the film surface.
[0039] Specifically, two surfaces of the composite conductive film in the thickness direction have different surface roughness Rz.
[0040] Based on the above technical solution, the surface with different roughness can increase the gap in the matching surface, and can also increase the adhesion of related active materials in the subsequent electrode to a certain extent.
[0041] Specifically, two surfaces of the composite conductive film in the thickness direction have different average widths Rsm of profile units and different surface roughness Rz.
[0042] Based on the above technical solution, the gap in the mating surface can be further increased; the surface with greater roughness is preferably set on the side with a larger average width of the surface contour, so that the gap formed by the contour unit can be coordinated to reserve more air retention space and reduce the vacuum degree after the film surface is rolled up and bonded.
[0043] Specifically, the average width of the contour units on one surface of the composite conductive film in the thickness direction is Rsm1, which ranges from 2 to 8 μm; the average width of the contour units on the other surface is Rsm2, which ranges from 0.2 to 2 μm.
[0044] Specifically, the roughness Rz1 of one surface of the composite conductive film in the thickness direction is 0.01-0.4 times the thickness of the corresponding composite conductive film, and the roughness Rz2 of the other surface is 0.1-0.6 times Rz1.
[0045] Specifically, the thickness of the support layer 1 is set to 3-50 μm, and the material thereof is a polymer material or a graphite film, and the surface roughness thereof is above 0.5 μm.
[0046] Specifically, the thickness of the conductive layer 2 is 0.05-3 μm, and the material thereof is one or a combination of gold, silver, copper, aluminum, nickel, and chromium.
[0047] This embodiment also provides a method for preparing a composite conductive film:
[0048] When the conductive layer 2 is disposed on a single surface of the support layer 1, a support layer 1 having an appropriate average width of the surface contour unit is selected, and the average width of the contour unit on the surface of the conductive layer 2 is controlled according to the average width of the contour unit on the surface of the support layer 1;
[0049] When the conductive layer 2 is disposed on both sides of the support layer 1, the average width of the contour unit that forms a difference on the surface of the conductive layer 2 on both sides is controlled.
[0050] Specifically, when the conductive layer 2 is provided on a single side of the support layer 1, the support layer 1 is processed by laser etching. Laser etching can effectively carve out two asymmetric surfaces on the support layer 1. On this basis, the metal layer is deposited by evaporation, magnetron deposition, etc., to obtain a composite conductive film surface determined by the surface morphology of the support layer 1.
[0051] Specifically, when the conductive layer 2 is provided on both sides of the support layer 1, the conductive layer 2 is coated on both sides in at least one of the following ways to form different surface profiles: increasing the temperature of the target material after evaporation; increasing the temperature of the target material after evaporation; or reducing the speed of the support layer; or reducing the distance between the support layer and the target material; or using laser etching to process the support layer.
[0052] Furthermore, the formation of the conductive layer 2 is based on the deposition of metal particles. The energy of the target particles deposited on the surface of the support layer 1 is different, and the size of the formed crystals is also different.
[0053] The relevant evaporation processes and equipment are existing well-known technologies. Those skilled in the art can adaptively adjust the relevant process parameters in combination with the above content of this application.
[0054] Of course, it is also applicable to other coating methods, such as sputtering, by adjusting the energy (RF power) of the bombarding target particles to obtain a larger crystal size, thereby obtaining a larger profile unit spacing and roughness.
[0055] For the single-sided formation of the conductive layer, the material of the support layer affects its surface roughness. For example, when the support layer is a polymer substrate, it has a relatively high flatness (0.05-0.1μm), so a larger profile spacing and roughness can be formed during the formation of the conductive layer. The material of the support layer can be selected from polyamide (PA), polyethylene terephthalate (PET), polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), acrylonitrile butadiene styrene copolymers (ABS), polybutylene ... At least one of poly(terephthalat, referred to as PBT), poly(p-phenyleneterephthamide, referred to as PPA), polyformaldehyde (Polyformaldehyde, referred to as POM), phenolic resin (Phenol-formaldehyde resin), polypropylene (PPE), polytetrafluoroethylene (Polytetrafluoroethylene, referred to as PTFE), polycarbonate (Polycarbonate, referred to as PC), etc.
[0056] For high temperature resistant substrates, such as graphite films, etc., since their surface roughness is relatively large and their profile width is relatively wide, they can be evaporated according to conventional processes; of course, since the surface roughness of commercially available pressed graphite films is generally above 0.5μm (the thickness of the graphite film is also much larger than the thickness of the conductive layer, and the thickness of the graphite film is generally above 20μm), and is preferably controlled to be above 2μm, a low vehicle speed solution can be further adopted to quickly form a conductive layer, and the surface particles of the conductive layer aggregate to form a larger crystal size, thereby having a wider profile unit spacing.
[0057] Comparative Example
[0058] Evaporation was performed according to the normal process, a 6μm support layer was selected, the vehicle speed was adaptively set to 4.5-6.5m / s, and the wire feeding (aluminum wire) speed was set to 300-600mm / min in combination with the vehicle speed. During this period, the current and voltage were controlled to make the evaporation boat light up (generally controlled in orange-yellow). The square resistance of the coated aluminum layer was 38-42mΩ / □, and it was about 1μm thick.
[0059] Preparation Example 1
[0060] The difference from the comparative example is that a 30 μm graphite film is selected as the support layer, and an aluminum layer of about 1 μm is evaporated on one side.
[0061] Preparation Example 2
[0062] The difference from Preparation 1 is that one side is evaporated at normal speed, while the other side is reduced to 1.5-2.5 m / s, and an aluminum layer of about 1 μm thick is evaporated on both sides.
[0063] Preparation Example 3
[0064] The difference from the comparative example is that the evaporation distance is reduced by 20 mm, and the other conditions remain basically unchanged, and an aluminum layer of about 1 μm is formed by evaporation.
[0065] Adhesion test: Use a blade to cut the roll sample and test the adhesion between the two films. When testing the bonded sample film, refer to the adhesion test method: Cover the upper and lower sides of the adhesive film sample with a layer of ethylene acrylic acid copolymer film, and then test the film under 1.3×105N / m 2 , hot press at 120℃ for 10s (or fix with double-sided tape), cool to room temperature, use as the traction fixing part of the tensile machine, and cut into 150mm×15mm strips. Finally, fix the ethylene acrylic acid copolymer film of the sample strip on the upper and lower clamps of the tensile machine respectively. After fixation, the two are peeled at an angle of 180° and a speed of 50mm / min, and the maximum value of the separation of the two layers of film is recorded.
[0066] The comparative example is 1.3N / 15mm;
[0067] Preparation Example 1 is 0.2N / 15mm; since the surface roughness of the graphite film is relatively high, after the single-sided aluminum layer is plated, the aluminum layer surface is relatively smooth due to the relatively fast aluminum plating speed, and the two layers of film can be easily separated.
[0068] Preparation Example 2 is 0.5N / 15mm; the coating surfaces formed after plating at different speeds on both sides have greatly different profiles. The crystal size on the side with a slow speed is larger and the crystals are more aggregated, so the surface on one side has a larger profile unit spacing, resulting in a difference in surface profiles on both sides;
[0069] Preparation Example 3 is 0.8N / 15mm; due to the reduction in the evaporation distance, the heat of the evaporated aluminum vapor increases, so the crystal size of the aluminum layer formed after plating is relatively larger, and small crystals are easy to recrystallize and aggregate to form large-sized crystals at high temperatures, so they have a larger contour unit spacing, which can improve the adhesion problem to a certain extent.
[0070] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite conductive film, characterized in that: The invention comprises a support layer (1) having two surfaces in the thickness direction; and a conductive layer (2) formed on at least one surface of the support layer (1); the two surfaces of the formed composite conductive film in the thickness direction have different contour morphologies, so as to form a gas-containing cavity (3) after the two layers of the composite conductive film are in contact.
2. A composite conductive film according to claim 1, characterized in that: The composite conductive film has different average widths Rsm of contour units on two surfaces in the thickness direction, and the difference is not less than 0.5 μm.
3. A composite conductive film according to claim 1, characterized in that: The composite conductive film has different surface roughness Rz on two surfaces in the thickness direction.
4. A composite conductive film according to claim 1, characterized in that: The two surfaces of the composite conductive film in the thickness direction have different average widths Rsm of profile units and different surface roughness Rz.
5. A composite conductive film as claimed in claim 2, characterized in that: The average width of the contour units on one surface of the composite conductive film in the thickness direction is Rsm1, which ranges from 2 to 8 μm; the average width of the contour units on the other surface is Rsm2, which ranges from 0.2 to 2 μm.
6. A composite conductive film as claimed in claim 3, characterized in that: The roughness Rz1 of one surface of the composite conductive film in the thickness direction is 0.01-0.4 times the thickness of the corresponding composite conductive film, and the roughness Rz2 of the other surface is 0.1-0.6 times Rz1.
7. A composite conductive film according to claim 1, characterized in that: The thickness of the support layer (1) is set to 3-50 μm, and its material is a polymer material or a graphite film, and its surface roughness is above 0.5 μm.
8. The composite conductive film according to claim 1, characterized in that: The thickness of the conductive layer (2) is 0.05-3 μm, and its material is one or a combination of gold, silver, copper, aluminum, nickel, and chromium.
9. A method for preparing a composite conductive film according to any one of claims 1 to 8, characterized in that: When the conductive layer (2) is disposed on a single surface of the support layer (1), a support layer (1) having an appropriate average width of the surface contour units is selected, and the average width of the contour units on the surface of the conductive layer (2) is controlled according to the average width of the contour units on the surface of the support layer (1); When the conductive layer (2) is arranged on both sides of the support layer (1), the average width of the contour unit formed by the difference in the surface of the conductive layer (2) on both sides is controlled.
10. The method for preparing a composite conductive film according to claim 9, characterized in that: When the conductive layer (2) is arranged on both sides of the support layer (1), the conductive layer (2) is plated on both sides in at least one of the following ways to form different surface profiles: increasing the temperature of the target material after evaporation; or reducing the speed of the support layer; or reducing the distance between the support layer and the target material; or using laser etching to process the support layer.
Citation Information
Patent Citations
Method of manufacturing wound battery
CN110364659A
Manufacturing method of flexible composite current collector
CN111048787A
Composite current collector, electrode sheet, battery core and secondary battery
CN112151810A
Composite current collector and preparation method thereof, lithium ion battery and vehicle
CN114597418A
Composite current collector and preparation process thereof
CN117374290A